Clinicians' experiences on patients' demands and shared decision making in Finnish specialized mental health care - Hilden Hanna-Mari; Hautamäki Lotta; Korkeila Jyrki (TAYLOR & FRANCIS LTD, 2022)
Purpose
Psychiatric patients' awareness of treatments options and their possibilities to influence their care has increased. For the clinicians, the management of evidence-based care, as well as organizational and resource aspects, set different goals for the clinical encounter. In this article we are focusing on the clinicians' experiences and ask: How do the clinicians view situations in which there is a conflict between patients' individual needs and goals and other aspects in decision-making?
Materials and methods
We implemented a qualitative study of 13 thematic semi-structured interviews with clinicians working in psychiatry. We used discourse analysis to investigate how the clinician view the doctor-patient interaction.
Results
We identified three discources which were termed the medical standpoint, the psychodynamic standpoint and the standpoint of the patient's experience.
Conclusions
In their talk, the clinicians use the three discources to make sense of the diverse expectations from both the patient and the mental health care system. The three discources also reflect different aspects in psychiatric treatment cultures, such as evidence-based medicine, the ideal of patient-centeredness, therapeutic interaction and organizational requirements.